Effects of diet mix time on growth performance of finishing pigs fed Ractopamine HCl - Paulk, C.B.; McKinney, Leland J.; Hancock, Joe D.; Williams, S.M.; Issa, S.; Gugle, Terry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to determine the effects of mix uniformity for diets with Ractopamine HCl (RAC) (Paylean; Elanco Animal Health, Greenfield, IN) when fed to finishing pigs. In Exp. 1, a total of 200 pigs (PIC TR4 × 1050; average BW of 198.4 lb) were used in a 33-d growth assay arranged in a randomized complete-block design with 5 pigs per pen and 8 pens per treatment. Treatments were a corn-soybean meal-based control diet mixed for 360 sec and the mixed control diet with 9 g/ton RAC added before additional mixing for 0, 30, 120, and 360 sec. Thus, this experiment was designed to determine the effects of nutrient utilization from a thoroughly mixed diet with a potential non-uniform distribution of RAC. Pigs fed diets with RAC had improved (P < 0.05) ADG, F/G, final BW, HCW, dressing percentage, backfat thickness, loin depth, and percentage carcass lean compared with control pigs. Increasing mix time from 0 to 360 sec decreased CV for Chromium (Cr) from 67 to 12%, but had no effect on the response to RAC for any growth or carcass measurement. In Exp. 2, a total of 160 pigs (PIC TR4 × 1050; average BW of 205 lb) were used in a 27-d growth assay arranged in a completely randomized design with 2 pigs per pen and 16 pens per treatment. Treatments were a corn-soybean meal-based control mixed for 360 sec and control diets with 9 g/ton RAC mixed for 0, 30, 120, and 360 sec. Thus, this experiment was designed to determine the combined effects of potentially nonuniform distribution of both nutrients and RAC. The use of RAC increased (P < 0.01) ADG, F/G, final BW, HCW, dressing percentage, percentage lean, and loin depth. Increasing mix times from 0 to 360 sec decreased CV for salt from 51 to 12% with no significant effect on ADG, F/G, HCW, dressing percentage, backfat thickness, loin depth, or percentage lean. In conclusion, increasing mix time of diets from 0 to 360 sec did not significantly affect the response of finishing pigs to RAC, but in Exp. 2 a mix time of 120 sec for the complete diet and RAC (CV of 15%) resulted in the numerically lowest (quadratic, P < 0.15) F/G.
Keywords: Swine; Diet CV; Mix time; Finishing pig; Ractopamine HCl